A Numerical Analysis of the Effect of Corrugated Surface Profile on Heat Transfer in Turbulent Flow Through a Rectangular Mini-Channel - Mansur Mustafaoğlu (nasiri Khalaji); Muhammet Kaan Yeşilyurt (MANAS: Journal of Engineering)
Mini channels have the potential to provide high heat transfer efficiency in a variety of applications. However, due to their small size, higher pressure drop occurs. Therefore, a balance needs to be established between heat transfer improvement and pumping power requirements. In the present study the effect of corrugated surface profile on heat transfer and flow characteristics were numerically investigated under turbulent flow conditions in a rectangular cross-section mini-channel through Computational Fluid Dynamics (CFD) simulations using the ANSYS Fluent 2019 software. The study employed. The mini-channel had a total length of 26 mm, with the left and right side walls consisting of 3 mm straight sections at the inlet and outlet, and a 19 mm corrugated section in the middle while the top and bottom sides are straight end to end. Optimum values for heat transfer and pressure drop were investigated through CFD analyses by varying the profile of the corrugated section of the side walls between 0.5, 1 and 2 mm for air and water fluids. It was determined that the pressure drop for air varied between approximately 850-1250 Pa whereas for water it varied between 1300-1900 Pa. The Nusselt number increased by 3.27% for air, from 12.2 to 12.6, and for water, it increased by 2.17%, from 13.36 to 13.65. Results showed that the corrugated surface improved heat transfer by increasing turbulence and mixing with the flow, but also significantly increases the pressure drop.